Effects of crocin and zinc chloride on blood levels of zinc and metabolic and oxidative parameters in streptozotocin-induced diabetic rats - Siamak Asri-Rezaei; Esmaeal Tamaddonfard; Behnaz Gasemsoltani-Momtaz; Amir Erfanparast; Sima Gholamalipour (Mashhad University of Medical Sciences, 2015)
Objectives:Crocin is one of constituents of saffron and has antioxidant property. Zinc chloride is one of the common compounds of zinc with antioxidant activity. The present study was aimed to investigate separate and combined treatment effects of crocin and zinc chloride on blood levels of zinc and metabolic and oxidative parameters in diabetic rats. Materials and Methods:Diabetes was induced by intraperitoneal (i.p.) injection of 50 mg/kg of streptozotocin (STZ) and was confirmed by blood glucose levels higher than 250 mg/dL. After confirmation of diabetes, injections (i.p.) of crocin and zinc chloride were performed for six weeks. At the end of the experiment, blood levels of zinc, glucose, insulin, malodialdehyde (MDA), and total antioxidant capacity (TAC) were measured. ‎ Results:Crocin (25 and 50 mg/kg) and zinc chloride (5 mg/kg) significantly recovered the decreased levels of zinc, insulin, and TAC and improved the increased levels of glucose and MDA in STZ-induced diabetic rats. In a combination treatment performed with an ineffective dose of crocin (12.5 mg/kg) and a low dose of zinc chloride (1.25 mg/kg), improving effects were observed on the above-mentioned biochemical parameters.‎ Conclusions: The results indicated that separate and combined treatments with crocin and zinc chloride produced improving effects on the blood levels of zinc, glucose, insulin, MDA and TAC in STZ-induced diabetic rats.‎